Can signal delay and advertising lead to profit? A study on sporting - Wu, Yannian; Yim, Brian H.; Lu, Chaoyun; Mao, Luke; Zhang, James J. (Frontiers in Psychology, 2023)
Live sporting event streaming (LSES) is becoming popular not only among consumers but also among sponsors. Despite being in an exploratory stage, its profit model has become a hot spot for enterprises and scholars. To promote financial sustainability, we analyzed the internal mechanism of profitability in LSES based on stimulus-organism-response (SOR) theory and two-sided market characteristics. Specifically, we considered exposure to ads and signal delay the stimuli (S), arousal and attention as the organism variables (O), and intention to become a paying subscriber as the response (R). We used an online survey questionnaire to collect data from 490 Chinese LSES viewers during the 2021 European Cup. We used SPSS Amos v. 26 to conduct structural equation modeling (SEM) and bootstrapping to test the model. The results show that the direct paths from exposure to ads and signal delay to behavioral intention were not significant and that these relationships only became significant via the mediating variables of arousal and attention. Compared to exposure to ads, signal delay had a stronger indirect effect on behavioral intention. Arousal and attention generated a chain intermediary mechanism in which the presence of attention was necessary.